Pulmonary pharmacodynamics of an anti-GM-CSFRα antibody enables therapeutic dosing that limits exposure in the lung. Issue 7 (2nd October 2016) - Campbell, Jamie; Nys, Josquin; Eghobamien, Laura; Cohen, E. Suzanne; Robinson, Matthew J.; Sleeman, Matthew A.
ABSTRACT: Pulmonary alveolar proteinosis is associated with impaired alveolar macrophage differentiation due to genetic defects in the granulocyte macrophage colony-stimulating factor (GM-CSF) axis or autoantibody blockade of GM-CSF. The anti-GM-CSFRα antibody mavrilimumab has shown clinical benefit in patients with rheumatoid arthritis, but with no accompanying pulmonary pathology observed to date. We aimed to model systemic versus pulmonary pharmacodynamics of an anti-GM-CSFRα antibody to understand the pharmacology that contributes to this therapeutic margin. Mice were dosed intraperitoneal with anti-GM-CSFRα antibody, and pharmacodynamics bioassays for GM-CSFRα inhibition performed on blood and bronchoalveolar lavage (BAL) cells to quantify coverage in the circulation and lung, respectively. A single dose of 3 mg/kg of the anti-GM-CSFRα antibody saturated the systemic cellular pool, but dosing up to 10 times higher had no effect on the responsiveness of BAL cells to GM-CSF. Continued administration of this dose of anti-GM-CSFRα antibody for 7 consecutive days also had no inhibitory effect on these cells. Partial inhibition of GM-CSFRα function on cells from the BAL was only observed after dosing for 5 or 7 consecutive days at 30 mg/kg, 10-fold higher than the proposed therapeutic dose. In conclusion, dosing with anti-GM-CSFRα antibody using regimes that saturate circulating cells, and have been shown to be efficacious in inflammatory arthritis models, did not lead to complete blockade of the alveolar macrophages response to GM-CSF. This suggests a significant therapeutic window is possible with GM-CSF axis inhibition.